Geopolitical Change in the World System : : The Emergence of Corridors and Environmental Orders - Hiwa Majid Khalil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The world is turning into an environmental, political, and economic upheaval. The ideological and superpower conflicts throughout the twentieth century created some orders on the international level, most notably the Cold War’s bipolar order and the post-Cold War unipolar order, which was recognized as the New World Order. Besides these orders, more or less, there was another order called a regional order. However, by entering the 20th century, China's rise as an economic power, the importance of energy to revive the economy and how to transfer this energy to other parts of the world on the one hand, and climate change that is causing environmental disasters on the other, the world seems to be moving towards a new order, which can be called the ‘Corridors Order’ and the ‘Environmental Order’. This research includes three sections. The first section is a gateway to presenting the topic; the second topic focuses on the corridors and their order; and the third one deals with the environmental order. Theoretically, the two orders are separated, but practically, they are mutually connected.